P26. Tibia fracture in mice as a model of Complex Regional Pain Syndrome (CRPS). Issue 8 (August 2015) - Ibrahim, A.; Lozano, F. Escolano; Hirsch, S.; Birklein, F.; Schlereth, T.
<x xml:space="preserve">Abstract</x> Introduction Complex Regional Pain Syndrome (CRPS) occurs after limb trauma, and is accompanied by inflammatory symptoms, motor abnormalities, sensory changes, pain and hyperalgesia. Aim We want to establish a mouse fracture model for CRPS in our lab resembling the symptoms seen in humans. Methods Wild type (WT) mice underwent tibial fracture and casting for 3 weeks. After cast removal, the post-traumatic inflammatory symptoms were tested and observed over time. We measured paw temperature, paw thickness, weight bearing of the paws, mechanical allodynia with von Frey hairs, heat pain thresholds with the Hargreaves method and cold allodynia with acetone. Results Mice reliably generated hindpaw warmth, edema, mechanical, hot and cold allodynia, as well as unweighting (as a measure of spontaneous pain); which regularly resolved after 10 weeks. Conclusion We have developed a model for a standard closed experimental fracture in the mouse tibia and have been able to quantify the complex post-traumatic symptoms. Our next goal is to use this model for the induction of an exaggerated posttraumatic response which is the underlying pathophysiology of human CRPS. Supported by the Hopp-Foundation.